Separating Real Incentives and Accountability - Ferdinand M. Vieider (Tinbergen Institute, 2008)
In experimental investigations of the effect of real incentives, accountability—the implicit or explicit expectation of a decision maker that she may have to justify her decisions in front of somebody else—is often confounded with the incentives themselves. This confounding of accountability with incentives makes causal attributions of any effects found problematic. We separate accountability and incentives, and find different effects. Accountability is found to reduce preference reversals between frames, for which incentives have no effect. Incentives on the other hand are found to reduce risk seeking for losses, where accountability has no effect. In a choice task between simple and compound events, accountability increases the preference for the simple event, while incentives have a weaker effect going in the opposite direction. It is thus shown that the confounding of accountability and incentives is relevant for studies on the effect of the latter, and that existing conclusions on the effect of incentives need to be reconsidered in light of this issue.
Keywords: C91; D71; D81; Z13; 330; Real v. hypothetical incentives; experimental economics; accountability; dual processing models; internal validity; simple and compound events; external validity; anchoring and adjustment; framing effects; Entscheidungstheorie; Glaubwürdigkeit; Ökonomischer Anreiz; Test; Theorie